Yellow fever in Brazil: thoughts and hypotheses on the emergence in previously free areas Fiebre amarilla en Brasil: reflexiones e hipótesis sobre la emergencia en áreas previamente libres Febre amarela no Brasil: reflexões e hipóteses sobre a emergência em áreas previamente livres - Pedro Fernando da Costa Vasconcelos (Revista de Saúde Pública, 2010)
This article describes and discusses factors associated to the reemergence of yellow fever and its transmission dynamics in the states of São Paulo (Southeastern Brazil) and Rio Grande do Sul (Southern) during 2008 and 2009. The following factors have played a pivotal role for the reemergence of yellow fever in these areas: large susceptible human population; high prevalence of vectors and primary hosts (non-human primates); favorable climate conditions, especially increased rainfall; emergence of a new genetic lineage; and circulation of people and/or monkeys infected by virus. There is a need for an effective surveillance program to prevent the reemergence of yellow fever in other Brazilian states. Son descritos y discutidos factores asociados con la emergencia y dinámica de la transmisión de la fiebre amarilla en los estados de Sao Paulo (Sureste de Brasil) y Rio Grande do Sul (Sur de Brasil) en los años 2008 y 2009. La interacción de los siguientes factores fue fundamental para la emergencia de fiebre amarilla en esos estados: la gran población humana susceptible; la elevada prevalencia de vectores y hospedadores (primates no humanos); condiciones climáticas favorables, principalmente el exceso de lluvias en el verano; la emergencia de un nuevo linaje viral; y la circulación de personas o monos infectados en fase virémica. Sólo un programa eficiente de vigilancia puede prevenir ocurrencias similares en esos estados brasileros. São descritos e discutidos fatores associados a emergência e dinâmica da transmissão da febre amarela nos estados de São Paulo e Rio Grande do Sul nos anos de 2008 e 2009. A interação dos seguintes fatores foi fundamental para a emergência de febre amarela nesses estados: a grande população humana suscetível; a elevada prevalência de vetores e hospedeiros (primatas não humanos); condições climáticas favoráveis, sobretudo o excesso de chuvas no verão; a emergência de uma nova linhagem viral; e a circulação de pessoas ou macacos infectados em fase virêmica. Apenas um programa eficiente de vigilância pode prevenir ocorrências similares nesses estados brasileiros.